Suitability of Rehabilitation Locations and Mangrove Growth on the Sunda Strait Coast, Case Study of Panimbangjaya Village, Pandeglang Regency, Banten Province - Susanto, Adi; Nurdin, Hery Sutrawan; Khalifa, Muta Ali; Munandar, Erik; Syafrie, Hendrawan; Alansar, Toufik; Sulistyono, Bakti; Raihan, Ahmad (Agrikan Jurnal Agribisnis Perikanan, 2024)
The coast of the Sunda Strait is vulnerable to the impacts of climate change and tsunami disasters, such as what happened in 2018. The most severe impact of the tsunami waves was reported by the people in Panimbang District and Sumur District. The condition of mangrove forests which continues to be degraded is unable to reduce the energy of tsunami waves so the losses are even greater. This research aims to evaluate mangrove rehabilitation activities carried out in Panimbangjaya Village, Panimbang District. Determination of rehabilitation locations is based on feasibility criteria taking into account environmental parameters and water quality. In the four month phase after planting on 1 ha of land, the growth of the planted mangrove seedlings was very good with a survival rate reaching 94%. However, the long dry season due to El-Nino caused dryness in the rehabilitation area and seedling death could not be avoided. The surviving seedlings have been able to adapt and continue to grow to a height of up to 75 cm. One year after planting, the survival rate is 25%.